ANALISIS PENYUSUNAN ANGGARAN OPERASIONAL SEBAGAI ALAT BANTU PENGENDALIAN PADA RM PRAMU BANDAR LOR KOTA KEDIRI - Panutur , Nugro Indah; Puspasari, Ismayantika Dyah; Widodo, Moch.Wahyu (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
This study airms to control excessive activities in financial terms at the RM PRAMU, by using a quantitative approach ang using forecasting methods and standard test menthods for forecasting errors as data analysis techniques. The results of this study are (1) RM PRAMU does not calculate the cost of goods manufactured, calculate the cost of production and determine the selling price of products, the calculation of overhead and what is done by RM PRAMU only calculates with a simple method or the results of sales are reduced by expenses. (2) The arrangement that should be implemented by RM PRAMU is using three methods, namely the moment method, the parabolic quadratic method, the least squares method and is tested using the standard error of forecasting (SKP) to determine which method has the minimum value.